Kontribusi Pajak Daerah Dan Retribusi Daerah Terhadap Peningkatan Pendapatan Asli Daerah Dalam Rangka Pelaksanaan Otonomi Daerah - Frenadin Adegustara; Syofiarti '; Titin Fatimah (Jurnal Ilmu Hukum, 2010)
Crash of regional autonomy has changed the paradigmof local governance. With these changes regions aregiven broad authority to regulate in the area of gover-nance including managing the financial resources ofexisting sources. Income is one of the major sourcesof regional funding within the framework of the imple-mentation of decentralization. Regional taxes andlevies have a very important role in supporting effortsto increase revenue (PAD). For collection of local taxesand levies are implemented by regulations issued localregulations. impacts that arise then are number ofnew regulations to appear the regulation of taxes andcharges of disrupting public and entrepreneurs createdthe conditions are not conducive to economic deve-lopment and national investment. In addition, regu-lations that lead to the occurrence of new levies, whichin turn creates a high cost economy the nationaleconomic burden. The fact that there are many rules,regulations revoked by the Government accordancewith the authority granted by the Act that the Govern-ment is authorized to evaluate each generated localregulations.